A CGPS view of the ISM towards HD 192281 - Arnal, Edmundo Marcelo (2011)
Massive stars are known to have a profound impact on their surroundings through their high ionizing radiation, their strong stellar winds, and their eventual final explosion as supernovae. Within the area surveyed by the CGPS project there are 87 O-type stars and 36 Galactic Wolf-Rayet stars. Therefore, the CGPS is an ideal database to study, in a large number of stellar targets, the interaction of massive stars (and their descendants) with their surroundings. In this paper we report on a study carried out towards the massive stars HD 192281. A shell-like structure, detectable at radio continuum, infrared and neutral hydrogen wavelengths, is found to be associated with this star.